ЖИСМОНИЙ ТАРБИЯ ВА СПОРТ СОҲАСИДА МАЛАКАЛИ МУТАХАССИСЛАР ТАЙЁРЛАШ ТИЗИМИНИ РИВОЖЛАНТИРИШ - Еримбетов, Б.Қ. (SCIENCE and SOCIETY, 2022)
This article analyzes the need to train qualified specialists in the field of physical culture and sports, as well as the role of sports educational institutions in this process.
Keywords: physical education; sports; education; system; non-governmental educational institutions; free economy; democratic society